37.5k views
1 vote
What are the factors of the expression below? -x+2x+35

What are the factors of the expression below? -x+2x+35-example-1
User Freshblood
by
5.8k points

1 Answer

2 votes

Answer:

A

Explanation:

Given

- x² + 2x + 35 ← factor out - 1 from each term

= - 1 (x² - 2x - 35)

To factor the quadratic inside the parenthesis

Consider the factors of the constant term (- 35) which sum to give the coefficient of the x- term (- 2)

The factors are - 7 and + 5

since - 7 × + 5 = - 35 and - 7 + 5 = - 2, hence

x² - 2x - 35 = (x + 5)(x - 7)

- x² + 2x + 35 = - 1 (x + 5)(x - 7) → A

User Double
by
4.9k points